2018
DOI: 10.1002/smll.201801536
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Improved Conductivity of Double‐Chain Polymer Network Binder for High Sulfur Loading Lithium–Sulfur Batteries with a Low Electrolyte/Sulfur Ratio

Abstract: Binders have been considered to play a key role in realizing high-energy-density lithium-sulfur batteries. However, the accompanying problems of limited conductivity and inferior affinity of soluble polysulfide intermediates bring down their comprehensive performance for practical applications. Herein, the synthesis of a novel double-chain polymer network (DCP) binder by polymerizing 4,4'-biphenyldisulfonic acid connected pyrrole monomer onto viscous sodium carboxymethyl cellulose matrix, yielding a primary cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 45 publications
0
54
0
1
Order By: Relevance
“…It was reported that some common conductive polymers such as polyaniline (PANI), [102] polypyrrole (Ppy), [103,104] PEDOT:PSS [105] are too rigid to sever as good binder. [39] It is noted that the introduction of soft segments or soft polymers inevitably reduces the electric conductivity of the binder. For example, poly(9,9dioctylfluorene-co-fluorenone-co-methylbenzoic ester) (PFM) was designed, in which the methylbenzoic ester segment was responsible for enhancing the elasticity, while the octyl side chains and fluorenone functional groups provided high conductivity.…”
Section: Improvement Of the Electron And Ion Transportmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that some common conductive polymers such as polyaniline (PANI), [102] polypyrrole (Ppy), [103,104] PEDOT:PSS [105] are too rigid to sever as good binder. [39] It is noted that the introduction of soft segments or soft polymers inevitably reduces the electric conductivity of the binder. For example, poly(9,9dioctylfluorene-co-fluorenone-co-methylbenzoic ester) (PFM) was designed, in which the methylbenzoic ester segment was responsible for enhancing the elasticity, while the octyl side chains and fluorenone functional groups provided high conductivity.…”
Section: Improvement Of the Electron And Ion Transportmentioning
confidence: 99%
“…The binder in Li-S batteries has experienced a remarkable evolution in terms of functions, from fundamental structural and mechanical stabilizer (linear, hybrid, [30] dendrimer, [31] and crossedlinked binder [32,33] ) to versatile functions of polysulfide immobilization (polymer with functional groups [34][35][36] or cation groups [37] ) and facilitation of electron transport on the basis of conductive polymer. [38,39] It opens up the research of multifunctional binder. The analogous development route in the binder is found in Na-S batteries.…”
Section: Structural and Mechanical Stabilizermentioning
confidence: 99%
See 2 more Smart Citations
“…Binders, as one of the most important electrode components, play a crucial role in resolving these issues. However, the traditional binder, polyvinylidene fluoride (PVDF), offers weak adhesion strength, requires the hazardous and volatile solvent N ‐methyl pyrrolidinone (NMP), and provides poor adsorption for LiPS and low Li‐ion conductivity . In contrast, water‐soluble binders have the advantages of environmental benignity and fewer safety concerns.…”
Section: Introductionmentioning
confidence: 99%